THE APPLICATION OF PREVIEW, READ, WRITE, AND RECITE (PRWR) METHOD TO IMPROVE STUDENT’S ACHIEVEMENT IN READING RECOUNT TEXT - Rahmat Nasution; Rahmah (Universitas Negeri Medan, 2014)
The objective of this research is to find out whether the application Preview, Read,Write, and Recite (PRWR) method improve student’s achievement in readingrecount text. This research applied classroom action research model. This studywas done in six meetings. The subject of this study was first year of SMAN 1Delitua. Primary data were collected by giving 20 questions of multiple-choicetest, the aspects contained in the tests focused on generic structure, main ideas,factual information, and Secondary data were collected by (interview, observationsheet, and questionnaire sheet. Based on analysis data, it was found that thestudent’s achievement improved. It could be seen from the comparison of result inthe orientation test and the cycle test I and II. There were only 9 students who hadpassed minimum criteria KKM in orientation test (75). The improvement showedthat in cycle I and II, based on the total average score it was 16 (42,4%) up to 26(78,7%) in cycle II, The secondary data gathered from interview, observationsheet, and questionnaire sheet, showed that students’ expression and enthusiasticalso improved. Thus, it was found that the applications of Preview, Read, Write,and Recite (PRWR) method in process of teaching improved students’achievement in reading recount text. It is suggested that English teachers applyPRWR method in teaching reading recount text.